Community-based waste management model in DKI Jakarta - Husen, Achmad; Samadi, Samadi (Linguistics and Culture Review, 2021)
The waste management that has been running in Jakarta today, where the majority still use the collect-transport-dump system, has been changed to a waste management approach that integrates the roles of the community, government and the private sector. This study aims to find a suitable waste management model for the DKI Jakarta Province. The research method used was descriptive analysis and a research and development approach. The informants are respondents consist of government officials related to waste management (Environmental Service), community leaders and local waste management activists. The results of the study show that The community based waste management model has so far proved to work when there is full Local Authority support and success is possible when the members of Local Organizations offering the service are form within the same community. The model has not only addressed the environmental problems resulting from poor waste management but has to a great extent contributed to the establishment of local good environment condition standards. Although the government programs in its infancy the results achieved so far indicate great potential for the improvement of the living environment through processes that are managed by communities.